Fagleksikografens forskellige brugergrupper med specielt henblik på beslutningstagere og disses rådgivere - Kaufmann, Uwe (Nordiske Studier i Leksikografi, 1997)
The basic aim of dictionaries is to mediate relevant and correct information to intended users. Included in this objective is that the information must be easily obtainable and easily understood. This aim seems obvious but practice shows it is not. First, many books are insufficient because oftheir content ofmisinformation. Secondly, the lexicographical and linguistic reweiting is often defective. Finally, active users of dictonaries makeup only a limited proportion ofthe potential user group. In my opinion it is possible to increase the quality of the dictionaries but how to convert latent users into active users?